Kristalisasi Butir Pancasila sebagai Fondasi Hukum Budaya di Republik Indonesia - Andrias, Maria Yeti; Zirhani Rumalean, Zonita (Universitas Ekasakti, 2023)
This paper aims to deepen the understanding of the Pancasila concept as a legal source within the context of national culture in the framework of the unitary state of the Republic of Indonesia. The research employs a documentary literature review approach. The analysis results conclude that